Characteristics of vaulting motion in world-class female pole vaulters in comparison with male pole vaulters at the same vaulting performance level - Arikawa, H.; Endo, T.; Tsukada, T.; Toyoshima, R.; Koyama, H.; Tauchi, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2016)
The purpose of this study was to clarify the characteristics of the vaulting motion of world-class female pole vaulters in comparison with male pole vaulters at the same vaulting performance level. The vaulting motions of 11 world-class female pole vaulters (FW group, records: 4.50—4.80 m) and 8 male pole vaulters who had records similar to the FW group (MV group, records: 4.40—4.80 m) were analyzed using three-dimensional motion analysis. The phase from one step before take-off to vaulting over the crossbar was analyzed. The FW group had the following characteristics. (1) Body weight was lower than that of the MV group. (2) The run-up and take-off velocities were slower than those of the MV group. (3) The distance between the top grip (right hand) and the lower tip of the pole was shorter than that of the MV group. (4) At take-off, the center of gravity was higher, and the pole angle relative to the ground was larger, than in the MV group. (5) In the pole bending phase after take-off, the shoulder flexion angle and the knee extension angle of the take-off leg were larger than in the MV group, thus increasing the moment of inertia of the body. Therefore, early backward tilting of the trunk was restricted. (6) In the pole straightening phase, the pole was extended earlier than in the MV group owing to the rapid extension of the shoulder joint and the rapid swing of the trunk. (7) At pole release, the body was in a more vertical position than in the MV group. These findings suggest that whereas the vaulting motions of the FW group were superior to those of the MV group, run-up velocity and pole length of the former were inferior.